Sequence-dependent elastic properties of DNA - Lankas, F; Sponer, J; Hobza, P; Langowski, J (Journal of molecular biology, 2000)
Harmonic elastic constants of 3-11 bp duplex DNA fragments were evaluated using four 5 ns unrestrained molecular dynamics simulation trajectories of 17 bp duplexes with explicit inclusion of solvent and counterions. All simulations were carried out with the Cornell et al. force-field and particle mesh Ewald method for long-range electrostatic interactions. The elastic constants including anisotropic bending and all coupling terms were derived by analyzing the correlations of fluctuations of structural properties along the trajectories. The following sequences have been considered: homopolymer d(ApA)(n) and d(GpG)(n), and alternating d(GPC)(n) and d(APT)(n). The calculated values of elastic constants are in very good overall agreement with experimental values for random sequences. The atomic-resolution molecular dynamics approach, however, reveals a pronounced sequence-dependence of the stretching and torsional rigidity of DNA, while sequence-dependence of the bending rigidity is smaller for the sequences considered. The earlier predicted twist-bend coupling emerged as the most important cross-term for fragments shorter than one helical turn. The calculated hydrodynamic relaxation times suggest that damping of bending motions may play a role in molecular dynamics simulations of long DNA fragments. A comparison of elasticity calculations using global and local helicoidal analyses is reported. The calculations reveal the importance of the fragment length definition. The present work shows that large-scale molecular dynamics simulations represent a unique source of data to study various aspects of DNA elasticity including its sequence-dependence.
Keywords: Base Sequence; Base Pairing; počítačová simulace; Solvents; statická elektřina; Oligodeoxyribonucleotides; Anisotropy; Elasticity; párování bází; DNA; pružnost; pohyb těles; Nucleic Acid Conformation; Algorithms; Computer Simulation; rozpouštědla; konformace nukleové kyseliny; voda; Motion; Water; anizotropie; oligodeoxyribonukleotidy; sekvence nukleotidů; Thermodynamics; algoritmy; termodynamika; Static Electricity